ANALISIS DAMPAK PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN DENGAN VARIABEL MODERATOR PADA GO-JEK - Parlin Sinaga (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the impact of GoJek's quality of service and price on customer satisfaction with Stie Tribuana student’s purchase intent as a moderate variable in the fifth semester. The population used in this survey is the consumers who used the Gojek transportation serviceThe study was conducted using a quantitative descriptive approach, and the nature of the study is a case study supported by the study. The essence of this study is descriptive study. H. The test is intended to explain and explain the nature of the situation that was present at the time the test was performed and to investigate the cause Based on the analysis results and reasoning of this study, we can conclude that there are four accepted hypotheses. In short, customer satisfaction and purchasing preferences for service are variables that adjust service levelsBased on the analysis results and reasoning of this study, we can conclude that there are four accepted hypotheses. In short, customer satisfaction and purchasing preferences for service are variables that adjust service levels. Customer satisfaction. Service variables are related to customer satisfaction, customer satisfaction with interest rates is a medium variable, and interest rate price variables are medium variables. Other hypotheses were rejected because the survey showed a significant association with the customer satisfaction variable, that is, the variable price did not affect customer satisfaction.